Increased resource use efficiency amplifies positive response of aquatic primary production to experimental warming. (11th October 2017) - Hood, James M.; Benstead, Jonathan P.; Cross, Wyatt F.; Huryn, Alexander D.; Johnson, Philip W.; Gíslason, Gísli M.; Junker, James R.; Nelson, Daniel; Ólafsson, Jón S.; Tran, Chau
Abstract: Climate warming is affecting the structure and function of river ecosystems, including their role in transforming and transporting carbon (C), nitrogen (N), and phosphorus (P). Predicting how river ecosystems respond to warming has been hindered by a dearth of information about how otherwise well‐studied physiological responses to temperature scale from organismal to ecosystem levels. We conducted an ecosystem‐level temperature manipulation to quantify how coupling of stream ecosystem metabolism and nutrient uptake responded to a realistic warming scenario. A ~3.3°C increase in mean water temperature altered coupling of C, N, and P fluxes in ways inconsistent with single‐species laboratory experiments. Net primary production tripled during the year of experimental warming, while whole‐stream N and P uptake rates did not change, resulting in 289% and 281% increases in autotrophic dissolved inorganic N and P use efficiency (UE), respectively. Increased ecosystem production was a product of unexpectedly large increases in mass‐specific net primary production and autotroph biomass, supported by (i) combined increases in resource availability (via N mineralization and N2 fixation) and (ii) elevated resource use efficiency, the latter associated with changes in community structure. These large changes in C and nutrient cycling could not have been predicted from the physiological effects of temperature alone. Our experiment provides clear ecosystem‐level evidence that warming can shift the balance between C and nutrient cycling in rivers, demonstrating that warming will alter the important role of in‐stream processes in C, N, and P transformations. Moreover, our results reveal a key role for nutrient supply and use efficiency in mediating responses of primary producers to climate warming. Abstract : The warming manipulation increased stream water temperatures by an average of 3.3°C relative to the previous year (a), while maintaining similar seasonality. During the year of the warming manipulation, gross primary production nearly tripled (b) and there was a shift in the autotroph community toward dominance by Ulva during June and July (c vs. d).